Producción de biosurfactantes lipopeptídicos por Bacillus spp. en fermentación en medios sólido y líquido - Valdés Velasco, Luisa Marcela (Universidad Autónoma Metropolitana, 2022)
The lipopeptide biosurfactants produced by Bacillus, have applications in different fields of industry. Lipopeptides have been mainly carried out in submerged fermentation which presents foaming associated with biosurfactant production. Besides, some increase in medium viscosity is due to the production of exopolysaccharides by some strains. Foaming and high viscosity decrease oxygen transfer, increasing the production costs and diminishing product concentration. On the other hand, solid-state fermentation does not present such problems and Reports of lipopeptide production in solid-state fermentation are scarce but satisfactory and have mostly used natural supports (non-inert material), agro-industrial residues, or complex culture media, which hinders recovery, purification, and analysis of the product. The aim of the work was to develop a bioprocess with higher LP production in solid-state fermentation with a defined medium adsorbed on an inert support such as polyurethane foam. The above facilitate the control of the bioprocess, recovery, analysis of the products, and comparison with submerged fermentation. In this way, identify and understand the relationship between secondary and primary metabolism and some limiting nutrients with the bioprocess. Part I of this work used Bacillus subtilis ATCC 6633 for the tests as improvement of the strain, selection of the most favorable solid support, and the effect of C/N on LP production. Polyurethane foam is the support that could allow the greatest lipopeptide production. The ammonium nitrate and C/N 17.1, was the most favorable condition for the bioprocess. For Part II, different strains were studied in solid and submerged fermentation, four wild and one mutant strain (unable to develop biofilm). The wild-type strains revealed a higher production of lipopeptides and biomass, glucose consumption, and a lower synthesis of primary metabolites in solid-state fermentation than in submerged. However, the mutant strain produced a slightly higher production of primary metabolites in solid fermentation than in submerged. The analysis of the carbon balance showed that the carbon flux is directed mainly to lipopeptides in solid-state fermentation, whereas, in submerged fermentation, it is directed to the production of primary metabolites. In the present work, a bioprocess is developed in solid-state fermentation with high lipopeptide production, mainly fengycin (2.7 g/L) and iturin (1.2 g/L) using a defined medium adsorbed on inert support by the Bacillus subtilis ATCC 21332. The concentrations reached are higher than those reported in the literature by wild strains. To the best of my knowledge, this is the first report that uses polyurethane foam in solid-state fermentation for lipopeptide production, facilitating the recovery and analysis of the product, as well as glucose and biomass. Furthermore, this is the first study to present the quantitative production of fengycin by solid fermentation.; Los biosurfactantes (BS) lipopeptídicos producidos por Bacillus tienen aplicaciones en diferentes áreas de la industria. Los lipopéptidos (LP) se han producido principalmente en fermentación líquida (FML), la cual presenta formación de espuma asociada con la producción de BS y un incremento en la viscosidad del medio debido a la producción de exopolisacáridos, lo que provoca una baja transferencia de oxígeno. Dichas situaciones aumentan los costos de producción y bajan la concentración del producto. Por otro lado, la fermentación sólida (FMS) no presenta dichos problemas y son escasos pero satisfactorios los reportes de producción de LP en este tipo de cultivo, los cuales, en su mayoría han utilizado soportes naturales (no inertes), residuos agrícolas o medios de cultivo complejos, que dificultan la recuperación, purificación y análisis del producto. El objetivo fue desarrollar un bioproceso con alta producción de LP en FMS utilizando un medio definido adsorbido en un soporte inerte como la espuma de poliuretano (PUF) para facilitar el control del bioproceso, recuperación, análisis de los productos y comparación con la FML. De esta forma, identificar y comprender la relación entre los metabolismos primario y secundario; y algunos nutrientes limitantes con el bioproceso, ya que poco se les ha investigado. En la parte I del trabajo se utilizó B. subtilis ATCC 6633 para las experimentaciones las cuales incluyen: mejorar la cepa por mutagénesis inducida, seleccionar el soporte inerte que más beneficia el bioproceso y evaluar el efecto C/N del medio de cultivo en la producción de los LP. Se encontró que la PUF, es el soporte que permitiría producir mayor cantidad de LP y se obtuvo que el nitrato de amonio y la relación C/N=17.1, es la condición que permitió la mayor concentración de LP. En la parte II se estudiaron diferentes cepas en FML y FMS, cuatro silvestres y una mutante (incapaz de desarrollar biopelícula). Las cepas silvestres revelaron una mayor producción de LP y biomasa, consumo de glucosa y una menor síntesis de metabolitos primarios en FMS que FML. Sin embargo, la cepa mutante presentó una producción ligeramente mayor de metabolitos primarios en FMS que FML. El análisis del balance de carbono mostró que el flujo de carbono se dirige principalmente a los LP en FMS, mientras que, en FML, se dirige a la producción de metabolitos primarios. Se desarrolló un bioproceso en FMS con alta producción de LP de fengicina (2.7 g/L) e iturina (1.2 g/L) utilizando un medio definido adsorbido en un soporte inerte por la cepa Bacillus subtilis ATCC 21332. Las concentraciones alcanzadas son mayores a las reportadas en la literatura por cepas silvestres. Este es el primer reporte que utiliza en FMS PUF en la producción de LP, facilitando la recuperación y análisis del producto como de glucosa y biomasa. Además, es el primer estudio que presenta la producción cuantitativa de fengicina por FMS.